Increased Use of Nutrition Fact Labels Was Associated With Confirmed COVID-19 Infections and Unfavorable Changes in Daily Life: Data Focusing on Quarantined and Hospitalized Patients - Hyang-im Baek; Jung Min Cho (Clinical nutrition research, 2025)
Nutrition fact labels (NFLs) are a simple way to help people improve their nutritional intake by making healthier food choices. This study aimed to evaluate NFL use and eating habit changes among quarantined and hospitalized coronavirus disease 2019 (COVID-19) patients during the pandemic. This cross-sectional study used data from the 2019 and 2020 Korean Community Health Surveys (KCHSs). Data were collected from 229,099 subjects in 2019 and 229,269 subjects in 2020. In the 2020 KCHS, data from 1,073 COVID-19 patients were included. NFL use was divided into 4 categories based on a questionnaire: affect, read, aware, and never heard. Among COVID-19 patients, 32.15% reported that they had not heard of NFLs (never heard group) compared to 44.36% of the healthy population (p < 0.001). A total of 35.1% of COVID-19 patients who reported daily life change scores of 20 or less were in the affect group compared to 23.8% of healthy subjects. In the affect group, the proportion of respondents who reported increased consumption of delivered food was 38.7% in the COVID-19 group, which was 17.1% higher than that in the never heard group (Cramér’s V = 0.257; p < 0.001). Respondents with increased consumption of fast food/soda showed a higher ratio of having never heard of NFLs among healthy subjects (28.5%) than among COVID-19 patients (22.5%; p = 0.043). Confirmed COVID-19 infections and more unfavorable daily life changes due to COVID-19 led to increased nutritional information seeking and NFL use.